The Relationship Between Cervicovaginal Infection, Human Papillomavirus Infection and Cervical Intraepithelial Neoplasia in Romanian Women - Anca Daniela Brăila; Cristian-Viorel Poalelungi; Cristina-Crenguţa Albu; Constantin Marian Damian; Laurențiu Mihai Dȋră; Andreea-Mariana Bănățeanu; Claudia Florina Bogdan-Andreescu (Diseases)
Cervical intraepithelial neoplasia (CIN) is a premalignant cervical condition closely linked to persistent high-risk HPV infection, a major risk factor for cervical cancer. This study aims to investigate the relationship between cervicovaginal infections, HPV infection, and CIN development in 94 Romanian women with cervical lesions. Comprehensive assessments included HPV genotyping, cytology, colposcopy, and histopathology. In 53.20% of cases, vaginal infections were identified, with Candida albicans most frequently associated with HPV. Histopathology revealed 48.94% low-grade CIN, 42.55% high-grade CIN, and 8.51% invasive carcinoma. There was a strong correlation between high-risk HPV types (especially HPV 16 and 18), colposcopic findings, histopathology, and age. This study emphasizes the mutual effect of cervicovaginal infections and HPV infection in increasing the risk of developing CIN and cervical cancer among Romanian women. Persistent infection with high-risk HPV types, particularly HPV 16 and 18, has been confirmed as a primary driver of CIN and cervical cancer progression.